Synthesis of novel organofunctional silicones and silanes for interface control - Stan, Sinziana Rodica (My University, 1999)
The synthesis and characterization of new organo-functional silicones bearing nitrilotriacetic acid chelating moieties is described. Several synthetic pathways were explored towards this goal and the most promising synthesis was used in order to obtain five different chelating silicones. These compounds formed insoluble films on aqueous surfaces. An investigation of the surface pressure exerted by these films was performed by employing a Langmuir trough. For comparison, a series of five new carboxylic acid-functional silicones was also synthesized and studied. The effect of molecular weight, type and position of functional group, and metal cation presence in the subphase are discussed. Possible conformations adopted by these polysiloxane derivative polymers at the surface were also presented. The design, synthesis, and characterization of small molecular weight organosilane linkers that can control hydrophobic - hydrophilic interfaces in wood - polyolefin composites by means of covalent bond formation is described. Several vinylallylsilane-based coupling agents were synthesized and their radical-initiated grafting onto polyethylene and squalane (a polyolefin mimic) was presented. One such organosilane, dimethyl(γ-hydroxypropyl)-vinylsilane, combined with a low molecular weight polyethylene-g -maleic anhydride oligomer, was used in order to reinforce wood - polyethylene composites and the mechanical properties of these materials were described.
Keywords: Chemistry; Chemistry